2002
DOI: 10.1159/000052829
|View full text |Cite
|
Sign up to set email alerts
|

The Aging Liver

Abstract: Background/Objective: Numerous age-related changes in hepatic structure and function have been described, although liver function seems to be quite well maintained in old age. Few consistent and reproducible observations and a lack of correlation between structural and functional data characterize the present state of our knowledge. In contrast to renal clearance, no equally reliable method exists to estimate hepatic drug clearance. The contribution of age to altered drug clearance in the elderly is difficult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…The reduced renal clearance of drugs that occurs with normal aging has been well described, and this phenomenon is likely to be more marked in aging recipients of older kidneys. Less appreciated are the changes that occur in hepatic metabolic capacity with age that may impact on hepatic drug clearance in older transplant recipients [97]. However, the extent of the impact of a given drug or drug protocol on the immune system affected by age is not currently known.…”
Section: Risk Of Cancer In the Elderly Transplant Recipientsmentioning
confidence: 99%
“…The reduced renal clearance of drugs that occurs with normal aging has been well described, and this phenomenon is likely to be more marked in aging recipients of older kidneys. Less appreciated are the changes that occur in hepatic metabolic capacity with age that may impact on hepatic drug clearance in older transplant recipients [97]. However, the extent of the impact of a given drug or drug protocol on the immune system affected by age is not currently known.…”
Section: Risk Of Cancer In the Elderly Transplant Recipientsmentioning
confidence: 99%
“…However, in rat and human studies it has been shown that with older age there is decreasing liver volume and blood flow [8][9][10][11]. Older livers may have impaired regenerative capabilities associated with shortened telomere length as well as altered oxidative and metabolic capacities [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolism and clearance of drugs are also changed in the elderly [12][13][14][15][16] (Table 2). Unfortunately, because elderly patients with comorbid conditions are excluded from many drug trials, the knowledge of drug metabolism is limited.…”
Section: Age-related Changes Affecting Pharmacokineticsmentioning
confidence: 99%
“…Hepatic metabolism in the elderly is not only related to age, but to lifestyle, genotype, hepatic blood flow, hepatic disease, and interactions with other medications. It may be reduced up to 30% to 50% in the elderly [14][15][16]. Hepatic metabolism occurs through one of two biotransformation systems.…”
Section: Age-related Changes Affecting Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation